Frequent lambda light chain gene rearrangement and expression in a Ly-1 B lymphoma with a productive kappa chain allele. - Hardy, R R (1986)
We describe here a murine Ly-1-bearing pre-B-cell tumor that, when induced for kappa light chain expression with bacterial lipopolysaccharide, also gives rise spontaneously to a few percent of cells expressing surface lambda light chains. These lambda-positive cells have undergone DNA rearrangements involving either V lambda 1 or V lambda 2 genes. Nearly all clones of lambda-bearing cells express mu and lambda on their surface (but not kappa). However, all these lambda-positive clones continue to transcribe kappa mRNA and synthesize internal kappa chains. Further, surface lambda-positive clones show JH rearrangements on one or both heavy chain chromosomes.